Electron States on the Rough GaAs (100) Surface, Formed by the Surface Acoustic Wave and Adsorbed Atoms - Рњ.Ya.В Seneta; R.Рњ.В Peleshchak; V.B.В Brytan (Журнал нано- та електронної фізики)
The theory of electron states is developed on the adsorbed surface of semiconductor which is bounded by the rough surface. The surface roughness are formed by both quasi-Rayleigh acoustic wave and adsorbed atoms. A spectrum of surface electron states on the adsorbed surface of GaAs semiconductor in the long-wavelength, resonanСЃe and short-wave approximations is founded, taking into account the interaction of the first three electron harmonics under the action of an acoustic quasi-Rayleigh wave. It is shown that the dependences of the energy band gap width on the surface of the semiconductor and the length of the spatial localization of electron wave function on the adsorbed atoms concentration in the interval have the nonmonotonic character.